2012
DOI: 10.1104/pp.112.200584
|View full text |Cite
|
Sign up to set email alerts
|

Individual Maize Chromosomes in the C3 Plant Oat Can Increase Bundle Sheath Cell Size and Vein Density    

Abstract: C4 photosynthesis has evolved in at least 66 lineages within the angiosperms and involves alterations to the biochemistry, cell biology, and development of leaves. The characteristic “Kranz” anatomy of most C4 leaves was discovered in the 1890s, but the genetic basis of these traits remains poorly defined. Oat × maize addition lines allow the effects of individual maize (Zea mays; C4) chromosomes to be investigated in an oat (Avena sativa; C3) genetic background. Here, we have determined the extent to which ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 66 publications
1
17
0
Order By: Relevance
“…The gene expression levels of the two key C4 enzymes in the OMAs, pyruvate orthophosphate dikinase (PPDK) on maize Chr6 and phosphoenolpyruvate carboxylase (PEPC) on Chr9, were not significantly changed compared with those in the maize B73 (Table 2 ). These data are consistent with the results of previous studies investigating the RNA and protein expression of the two genes in OMAs ( 42 , 43 ). However, the expression of other C4-related genes was changed in the oat genomic environment.…”
Section: Resultssupporting
confidence: 93%
“…The gene expression levels of the two key C4 enzymes in the OMAs, pyruvate orthophosphate dikinase (PPDK) on maize Chr6 and phosphoenolpyruvate carboxylase (PEPC) on Chr9, were not significantly changed compared with those in the maize B73 (Table 2 ). These data are consistent with the results of previous studies investigating the RNA and protein expression of the two genes in OMAs ( 42 , 43 ). However, the expression of other C4-related genes was changed in the oat genomic environment.…”
Section: Resultssupporting
confidence: 93%
“…The SCARECROW/SHORTROOT regulatory network has been determined to be one of the important components required for Kranz anatomy patterning because the leaves of C3 plants with mutated Scarecrow gene was normal, while in the C4 plants mutation in the same gene damaged the Kranz anatomy (Slewinski et al 2012 ; Wang et al 2013b ). Recently, it has been shown that introduction of maize chromosomes into oat could increase the BSC size and reduce vein spacing in C3 oat leaves demonstrating that the anatomy of C3 leaf can be modified (Tolley et al 2012 ). Moreover, a large effort has been put to screen sorghum (C4) mutants with increased vein spacing and rice (C3) mutants with reduced vein spacing so that the genes controlling vein spacing trait can be identified (Rizal et al 2012 ).…”
Section: Reviewmentioning
confidence: 99%
“…This may be why in oat-maize addition lines, the addition of individual maize chromosomes do not confer a functional C 4 photosynthetic mechanism (Tolley et al, 2012), because the oat C 4 program may have been suppressed or undergone degradation in leaves. However, in these studies, it is also important to take into consideration the caveats of the experiment itself.…”
Section: Evolution Of Kranz-type C4 Mechanism In Monocots: Revisitingmentioning
confidence: 99%